Microfoundations of institutions - Haack, Patrick; Sieweke, Jost; Wessel, Lauri (Emerald Publishing Limited, 2019)
The notion of microfoundations has received growing interest in neo-institutional theory (NIT) along with an increasing interest in microfoundational research in disciplines such as strategic management and organizational economics. However, despite reference to the same term, there are decisive differences in how microfoundations have been addressed across different disciplines.The aim of this double volume is to explore in more depth what the microfoundations of institutions are and what it takes to actually develop sound microfoundations. To this end, this double volume sets off by exploring the recent well-spring of micro-level research in NIT (i.e., research on the individual, practice and group level). While intimately related, micro-level research and microfoundations are not necessarily the same thing. Hence, the double volume seeks to bring to the fore different perspectives in micro-level research in order to tease out what these perspectives imply for building microfoundations, where they converge and where they diverge.
Includes index.
Keywords: New institutionalism (Social sciences); Macroeconomics; Self-help -- General; Society & social sciences